Multi-omic insights into the cellular response of Phaeodactylum tricornutum (Bacillariophyta) strains under grazing pressure - Liu, Chenqi; Li, Liang; Yang, Shuo; Wang, Mingye; Zhang, Hang; Li, Si (Frontiers in Plant Science, 2024)
Background/Aims: Phaeodactylum tricornutum, a model organism of diatoms, plays a crucial role in Earth's primary productivity. Investigating its cellular response to grazing pressure is highly significant for the marine ecological environment. Furthermore, the integration of multi-omics approaches has enhanced the understanding of its response mechanism. Methods: To assess the molecular and cellular responses of P.tricornutum to grazer presence, we conducted transcriptomic, proteomic, and metabolomic analyses, combined with phenotypic data from previous studies.Sequencing data were obtained by Illumina RNA sequencing, TMT Labeled Quantitative Proteomics and Non-targeted Metabolomics, and WGCNA analysis and statistical analysis were performed.Results: Among the differentially expressed genes, we observed complex expression patterns of the core genes involved in the phenotypic changes of P.tricornutum under grazing pressure across different strains and multi-omics datasets. These core genes primarily regulate the levels of various proteins and fatty acids, as well as the cellular response to diverse signals. Conclusion: Our research reveals the association of multi-omics in four strains responses to grazing effects in P.tricornutum.Grazing pressure significantly impacted cell growth, fatty acid composition, stress response, and the core genes involved in phenotype transformation.